Sports Shopping Motivations in Retail Stores: A Moderating Role of Sports Psychology - Selda Ene; Betül Özkaya , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
As a result of consumers' emotional attachment to the products and services, sports merchandise has also gained widespread popularity. This study investigates the relationship between brand awareness, brand loyalty, and consumers' shopping motivations at sports retail stores. A questionnaire was administered to the audience sample. A survey was administered to 350 Turkish consumers who shopped at sporting goods stores. The study's findings indicate that the moderating effect of sports psychology on shopping motivations, brand awareness, and brand loyalty is significant. This study is critical because previous research has not addressed this novel approach to developing findings for sports retail. This research has important theoretical and practical implications for advancing the literature and practice of sports retailing. The future directions proposed by this study are significant for future research contributions.